Factors associated with sleep quality among chinese women in Klang Valley, Malaysia - Lau, Chin Chin (2015)
Sleep problem is an emerging public health issue in Asia and Africa. Little information is available on sleep quality and its correlates among Chinese women. This study aimed to determine factors associated with sleep quality among Chinese women in Klang Valley, Malaysia. Factors including socio-demographic background (age, total family income, menopause status, education level), dietary factors (macronutrients, energy, B vitamins and calcium), anthropometry parameters (fat mass, lean mass and BMI) and lifestyle factors (physical activity, smoking and alcohol drinking). Data was from 263 Chinese women who participated in the 2012-2014 milk supplementation study. Few instruments were used for data collection. Sleep quality was measured using Pittsburgh Sleep Quality Index (PSQI). Questionnaire was used to collect demographic background. Current dietary intake and habitual calcium intake of participants were assessed by 3 days food records and Food Frequency Questionnaire (FFQ), respectively. Physical activity was measured using International Physical Activity Questionnaire (IPAQ). SPSS version 22.0 was used for statistical analysis of association and contribution of variables towards sleep quality. The mean age of study population was 50.3 years old, ranged from 30-69 years at time of study period. The prevalence of self-rated and objective assessed poor sleep quality was 12% and 27%, respectively. Mean sleep duration was 6.5 (1.4) hours. Older age (r=-0.299, p<0.01) and higher education attainment (r=0.219, p<0.05) were significantly correlated with short sleep duration among premenopausal participants. Higher dietary intake of energy (r=0.178, p<0.05) and fat (r=0.183, p<0.05) were significantly associated with higher total global PSQI score, indicating poor sleep quality among premenopausal participants. Higher intake of energy (r=0.196, p<0.05) and carbohydrate (r=0.188, p<0.05) were significantly associated with more sleep disturbances in premenopausal participants. None of the anthropometry parameters (BMI, lean mass or fat mass) and lifestyle factors (physical activity, cigarette smoking, alcohol drinking) were significantly correlated with sleep components including global PSQI score, sleep duration, sleep latency and sleep disturbance. Among postmenopausal, higher intake of calcium (r=-0.209, p<0.05) and physically active (r=0.258, p<0.01) were significantly associated with shorter time to fall asleep. Higher intake of fat (r=0.130, p<0.05), vitamin B1 (r=0.143, p<0.05) and vitamin B2 (r=0.150, p<0.05) were significantly associated with higher total global PSQI score, hence poorer sleep quality among participants. Older age (r=-0.172, p<0.01) and postmenopausal (r=-0.124, p<0.05) were significantly associated with short sleep duration among participants. Increased age (r=-0.169, p<0.01), premenopausal (r=0.175, p<0.01) and physically active (r=0.145, p<0.05) were significantly associated with shorter time to fall asleep. Higher intake of energy (r=0.131, p<0.05), carbohydrate (r=0.162, p<0.05), vitamin B2 (r=0.123, p<0.05) and vitamin B3 (r=0.133, p<0.05) were significantly associated with more sleep disturbance. Overall, the model explained approximately 29% of variance in global PSQI score contributed by dietary factors. Protein (t=-2.375, p<0.05) and fat (t=2.787, p<0.05) intake showed significant contributions towards sleep quality. In conclusion, these results indicated the importance of having adequate dietary protein and low dietary fat intake in promotion of good sleep quality. Incorporation of healthy diet may be the preferred approach to improve sleep quality among Chinese women in Klang Valley.